Regional differences in physicians’ behavior and factors influencing the intensity of PCSK9 inhibitor therapy with alirocumab: a subanalysis of the ODYSSEY APPRISE study - Banach, Maciej; Lewek, Joanna; Pol, Kaja; Rabczenko, Daniel; Balanescu, Serban M.; Blaha, Vladimir; Ceska, Richard; Jankowski, Piotr; Surma, Stanisław; Kolovou, Genovefa; Liberopoulos, Evangelos; Mitu, Florin; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: We aimed to compare the differences in physicians’ therapeutical decisions on alirocumab dose selection, and factors affecting these in CEE countries vs other countries included in the ODYSSEY APPRISE study. Methods: ODYSSEY APPRISE was a prospective, single-arm, phase 3b open-label (≥12 weeks to ≤30 months) study with alirocumab. Patients received alirocumab 75 or 150 mg every 2 weeks, with dose adjustment during the study based on physician's judgment. The CEE group in the study included Czech Republic, Greece, Hungary, Poland, Romania, Slovak Republic, and Slovenia, which we compared with the other 9 European countries (Austria, Belgium, Denmark, Finland, France, Germany, Italy, Spain, and Switzerland) plus Canada. Results: 921 patients on alirocumab were involved (mITT analysis), including 114 (12.4%) subjects from CEE countries. Therapy in CEE vs other countries was numerically more frequently started with lower alirocumab dose (75 mg) at the first visit (74.6 vs 68%, p=0.16). Since week 36, the higher dose was predominantly used in CEE patients (150 mg dose in 51.6% patients), which was maintained by the end of the study. Altogether, alirocumab dose was significantly more often increased by CEE physicians (54.1 vs 39.9%, p=0.013). Therefore, more patients achieved LDL-C goal at the end of the study (<55 mg/dl/1.4 mmol/L and 50% reduction of LDL-C: 32.5 vs 28.8%). The only factor significantly influencing the decision on dose of alirocumab was LDL-C level for both countries’ groups (CEE: 199.2 vs 175.3 mg/dL; p=0.019, other: 205.9 vs 171.6 mg/dL; p<0.001, for 150 and 75 mg of alirocumab, respectively) what was also confirmed in multivariable analysis (OR=1.10; 95%CI: 1.07-1.13). Conclusions: Despite larger unmet needs and regional disparities in LDL-C targets achievement in CEE countries, more physicians in this region tend to use higher doses of alirocumab, they are more prone to increase the dose, which is associated with a higher proportion of patients reaching LDL-C goals. The only factor that significantly influences decision whether to increase or decrease the dose of alirocumab is LDL-C.